THE PRESENCE AND CHARACTERISTIC OF LOGICAL-SEMANTIC, HEURISTIC, TACTICAL AND TECHNICAL ACTIONS AND OPERATIONS IN RESOLVING THE PROBLEMATIC PLAYING SITUATIONS OF HANDBALL PLAYERS DURING THE OFFENSE - Ahmetović Osman; Branimir Mikić; Djug Muris; Melika Muratović (Sport Scientific And Practical Aspects, 2025)
Scope and objective of this research is the presence and characteristics of heuristic, tactical and technical actions and operations of handball players in resolving the problematic playing situations during the offence at the B&H Handball Premier League official matches. Presence and analysis of the characteristics of heuristic, tactical and technical actions and the operations of handball players in resolving problematic playing situations was conducted based on four videotaped games of the regular Premier League and four handball teams. The study included 71 handball player of the B&H Premier League. The values derived variables defined problematic playing situations, tactical and technical actions and operations of handball players during the offense (positive and negative impact) at the match. B&H Premier League have produced ratings of their importance for success in the game (valued curve gradual scale based on expert ratings) and tracked the incidence of actual handball players’ play during four of the matches. The first part of research focused on determining the general structure of motor composition variables which defined aspects of resolving the problematic situations, tactical-technical actions and operations of handball players during the offense, it is important for the effectiveness of individual and cooperative playing to resolve the problematic situations. With multiple analysis of variance of variables defined aspects of handball players problematic playing situations, confirmed the appropriateness of their choices, which may introduce taxonomic alignment statistical significance for handball players by the type of cluster groups, team affiliation and position in the team.